Science, colonialism, and indigenous peoples : the cultural politics of law and knowledge - Whitt, Laurelyn (Cambridge ; $a New York, NY : Cambridge University Press, 2009)
At the intersection of indigenous studies, science studies, and legal studies lies a tense web of political issues of vital concern for the survival of indigenous nations. Numerous historians of science have documented the vital role of late 18th and 19th century science as a part of statecraft, a means of extending empire.
Originally published: 2009.
Includes bibliographical references and index.
Keywords: Indians of North America -- Legal status, laws, etc; Indigenous peoples -- Legal status, laws, etc; Intellectual property; Traditional ecological knowledge -- Law and legislation; Sociological jurisprudence; Indians of North America -- Legal status, laws, etc; Indigenous peoples -- Legal status, laws, etc; Intellectual property; Sociological jurisprudence; Traditional ecological knowledge -- Law and legislation